More alike than different: the Spanish and Irish labour markets before and after the crisis - Pablo Agnese; Pablo F. Salvador (IZA Journal of European Labor Studies, 2012)
Spain and Ireland might seem at first to feature very different labour markets, which go from very tight to very flexible labour conditions. Our analysis, however, goes beyond this simplistic argument and brings to light some important similarities. For this purpose, we estimate a dynamic multi-equation structural model for each country and offer two sets of dynamic simulations that account for the swings of the unemployment rates before and after the 2007 crisis. Our results suggest looking beyond the degree of flexibility in both labour markets and focusing instead on other variables usually neglected by more conventional approaches. In particular, such variables as the growth of capital stock, the growth of labour productivity, and demographics, succeed in explaining a great part of the changes in unemployment in both countries.
Keywords: E24; J21; E22; C32; 330; unemployment dynamics; structural multi-equation models; chain reaction theory; simulations; PIGS